Kedatangan Kristus Kedua Kali: Harapan Atau Ketakutan? (Tinjauan Dogmatis Mengenai Kedatangan Yesus Kedua Kali Dalam Teologi Reform) - Siregar, Richie Mikyano; Saragih, Elfrida (Sekolah Tinggi Diakones HKBP, 2025)
This article explores the Second Coming of Christ from a Reformed theological perspective, emphasizing its significance as a source of hope rather than fear for believers. Rooted in the authority of Scripture, Reformed theology understands eschatology as the culmination of God’s redemptive work, integrally connected to the doctrines summarized in TULIP. The study highlights the biblical meaning of Parousia as the visible, glorious return of Christ to judge humanity and inaugurate the new creation. While Scripture affirms that the exact time of Christ's return is unknown, it calls believers to live in vigilance, holiness, and obedience. Drawing from key passages such as Matthew 24, 1 Thessalonians 5, Titus 2, and Romans 13, the article underscores the practical implications of eschatological hope namely, moral readiness, spiritual sobriety, and active participation in God’s calling. Reformed churches teach that preparedness does not involve speculative predictions but faithful living grounded in grace. The study rejects sensationalist or fear-based eschatology and instead promotes a balanced understanding that motivates believers toward sanctification, perseverance, and joyful expectation. Ultimately, the Second Coming is presented as the fulfillment of God’s promise, inviting Christians to respond with faith, love, and steadfast commitment as they await Christ’s return with confidence and joy.